Analisis Kepatuhan Wajib Pajak Kendaraan Bermotor di Kota Payakumbuh (Studi Kasus SAMSAT Kota Payakumbuh) - Bulan, Bulan; Sofia, Nita; Ritonga, Mentari (Universitas Negeri Padang, 2025)
This research aims to determine the analysis of tax compliance of motor vehicles in Payakumbuh City. This research was conducted at Payakumbuh City SAMSAT office in Jl. Batimah Hall, District. East Payakumbuh., Payakumbuh town, West Sumatra. The form of research used is descriptive research with a quantitative approach. The data collection technique used was a questionnaire. The population of this research are motor vehicle taxpayers registered with SAMSAT Payakumbuh City. The sampling technique used Slovin's formula so that the number of samples obtained was 100 respondents. Based on the survey results, it can be concluded that the compliance level of Motor Vehicle Taxpayers in Payakumbuh SAMSAT City is quite good, indicated by the overall average result of 3.69 with a TCR of 73.66%. This means that taxpayer compliance in Payakumbuh City SAMSAT was well implemented, but not implemented optimally. Therefore, in the future, motor vehicle taxpayers in SAMSAT of Payakumbuh City are expected to further increase motor vehicle tax payment compliance to increase tax revenue in Payakumbuh City.